Sosialisasi Efisiensi Produksi dan Omzet Penjualan UMKM Kripik Singkong melalui Pemanfaatan Sistem Informasi Digital Marketing - Yuiana Trisanti; Citra Siwi Hanayanti; Anang Faktchur Rachman (Yayasan Literasi Sains Indonesia, 2023)
A prolonged pandemic as a result of the Corona virus is one form of threat that attacks many countries in the world. This pandemic has an impact on almost all sectors of life. One of the sectors affected apart from health is the economic sector. The economic sector cannot be separated from the shift where previously there were many conventional businesses, so in recent years it has begun to shift to digital business. In relation to MSMEs as one of the economic sub-sectors, inevitably they have to keep up with the times. The phenomenon that MSME products have constraints in terms of marketing so that many products are not sold, the use of traditional marketing strategies that have not reached a wide market share and a significant decline in income during the Covid-19 pandemic which has an impact on the low economic resilience of MSME actors. This PKM activity does not only carry out digital marketing activities for MSME products, but also solves the problems of cassava chip SMEs in marketing their products, from product design, packaging, to marketing through digital marketing. The objectives of this PKM are 1) to provide training to cassava chips SMEs how to design products to be attractive and provide different flavors that are liked by potential consumers; 2) provide training on how to package attractive and durable products; 3) provide training on how to market products through digital marketing so that the products produced are known to the wider community. The method used is in the form of training for MSME actors with clear output targets for each training subject.